2001
DOI: 10.1021/es001699b
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Prediction of the Detoxifying Properties of Humic Substances Related to Their Chemical Binding to Polycyclic Aromatic Hydrocarbons

Abstract: Effects of 27 different humic materials on the toxicity of polycyclic aromatic hydrocarbons (PAH) were studied for crustacean Daphnia magna. Sources included isolated humic acids, fulvic acids, and their combination from soil, peat, and freshwater. The PAH used were pyrene, fluoranthene, and anthracene. The observed reduction in toxicity of PAH in the presence of humic substances (HS) was shown to be a result of the detoxification effect caused by the chemical binding of PAH to HS and of the direct effect of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 28 publications
(37 reference statements)
2
58
0
1
Order By: Relevance
“…They are ubiquitous and result from the natural transformation of organic matter in soil and sediments. Among the effects of HS in the environment, increasing evidence indicates that they can act as natural attenuators of toxicity of heavy metals, surfactants, hydrocarbons, and organic oxidizers [2][3][4][5][6]. Elucidation of the detoxification mechanism by HS is of great interest [3,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…They are ubiquitous and result from the natural transformation of organic matter in soil and sediments. Among the effects of HS in the environment, increasing evidence indicates that they can act as natural attenuators of toxicity of heavy metals, surfactants, hydrocarbons, and organic oxidizers [2][3][4][5][6]. Elucidation of the detoxification mechanism by HS is of great interest [3,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Their chemical structure has not yet been defined precisely, but, in any case, the HA molecules contain a great number of aromatic rings, aliphatic chains and functional groups (carboxylic, phenolic, hydroxylic, carbonylic, amine and amides). Consequently, they are able to interact with a wide range of pollulants and can influence the solubility, transport, bioavailability and lower the toxicity of water solutions of dangerous organic compounds, such as polycyclic aromatic hydrocarbons (PAH), for aquatic organisms [3].…”
Section: Introductionmentioning
confidence: 99%
“…Radiochemical studies on PAH biodegradation in the presence of HA have demonstrated the biogenic formation of chemically bonded compounds [5]. Chemical degradation techniques made evident the presence of reaction products (mainly esters) formed between PAH acidic metabolites and HA [3,4]. Besides, it was observed that a fraction of the acidic PAH was not chemically bonded but formed inclusion compounds [6].…”
Section: Introductionmentioning
confidence: 99%
“…From the standpoint of bioavailability, interaction between dissolved organic matter (e.g. fulvic acids) and PAH has been reported to decrease PAH uptake and bioconcentration by, and/or toxicity to, higher organisms, for example Daphnia magna (Akkanen and Kukkonen, 2001;Perminova et al, 2001) and other aquatic organisms (Haitzer et al, 1999 & references therein). This, however, is in direct contrast to a spate of studies which have recently reported that addition of humic substances significantly stimulates microbial degradation of both polychlorinated biphenyls (Fava and Piccolo, 2002) and PAH (Haderlein et al, 2001;.…”
Section: Discussionmentioning
confidence: 99%